Application of heavy-ion-beam irradiation to breeding large rotifer. Issue 3 (14th January 2021) - Tsuneizumi, Kazuhide; Yamada, Mieko; Kim, Hee-Jin; Ichida, Hiroyuki; Ichinose, Katsunori; Sakakura, Yoshitaka; Suga, Koushirou; Hagiwara, Atsushi; Kawata, Miki; Katayama, Takashi; Tezuka, Nobuhiro; Kobayashi, Takanori; et al.
ABSTRACT: In larviculture facilities, rotifers are generally used as an initial food source, while a proper size of live feeds to connect rotifer and Artemia associated with fish larval growth is needed. The improper management of feed size and density induces mass mortality and abnormal development of fish larvae. To improve the survival and growth of target larvae, this study applied carbon and argon heavy-ion-beam irradiation in mutation breeding to select rotifer mutants with larger lorica sizes. The optimal irradiation conditions of heavy-ion beam were determined with lethality, reproductivity, mutant frequency, and morphometric characteristics. Among 56 large mutants, TYC78, TYC176, and TYA41 also showed active population growth. In conclusion, (1) heavy-ion-beam irradiation was defined as an efficient tool for mutagenesis of rotifers and (2) the aforementioned 3 lines that have larger lorica length and active population growth may be used as a countermeasure of live feed size gap during fish larviculcure. Graphical Abstract: